Experimental Analysis of Performance, Fuel Consumption, and Noise in Three Exhaust Configurations of a 145 cm³ Bore-Up Yamaha Jupiter Z - Mahendra Suryo Prabowo; Kriswanto Kriswanto; Abdurrahman Abdurrahman; Basyirun Basyirun; Ahmad Roziqin (Universitas Negeri Semarang, 2026)
Exhaust-system modification is a creative engineering problem because gains in engine performance can conflict with fuel-use efficiency and acoustic control. This study evaluates three exhaust configurations standard, free-flow, and Hight Performance Low Pollution Muffler (HPLPM) Mod 2 on a 145 cm³ bore-up Yamaha Jupiter Z engine to identify their multi-criteria trade-offs. A laboratory experiment measured torque and brake power using a chassis dynamometer, fuel consumption using a volumetric method, and A-weighted sound pressure level under controlled operating conditions. The free-flow configuration produced the highest maximum torque (13.10 N·m) and brake power (13.10 HP) and showed lower fuel consumption at low-to-medium engine speeds, although consumption increased at high speed. HPLPM Mod 2 consistently provided the strongest acoustic control, with a maximum measured level of 95.55 dB(A), compared with 101.85 dB(A) for the free-flow configuration. These results show that no single exhaust configuration simultaneously optimizes all performance criteria. The study contributes a multi-criteria experimental basis for creative exhaust-system selection: free-flow prioritizes performance, whereas HPLPM Mod 2 offers a more balanced compromise between performance and noise control.